Letter to Jane Tolmach from Glenn M. Anderson - Glenn M. Anderson:::::: (1965)
A letter dated October 5, 1965, from California Lieutenant Governor Glenn M. Anderson to Jane Tolmach of Oxnard, California. In the letter, Anderson thanks her for the invitation to attend the Ventura County Democratic Council's barbecue on September 26 and expresses that he and Mrs. Anderson greatly enjoyed the event. He closes by noting the warm and friendly atmosphere and extends his personal regards before signing as Lieutenant Governor.